Response to: Health Poverty Alleviation Project in Rural China: Impact on Poverty Vulnerability, Health Status, Healthcare Utilization, Health Expenditures [Response to Letter] - Li Z; Chen Y; Ding J (Dove Medical Press, 2024)
Zhipeng Li,1 Yuqian Chen,2 Jing Ding3 1Qu Qiubai School of Government, Changzhou University, Changzhou City, People’s Republic of China; 2School of Economics and Management, Shanghai University of Political Science and Law, Shanghai, People’s Republic of China; 3School of Public Economics and Administration, Shanghai University of Finance and Economics, Shanghai, People’s Republic of ChinaCorrespondence: Yuqian Chen, Affiliated School of Economics and Management, Shanghai University of Political Science and Law, No. 7989 Waiqingsong Road, Qingpu District, Shanghai, 201701, People’s Republic of China, Tel +8618502116053, Fax +862139227342, Email yvqianc@163.com